THE INFLUENCE OF AFFILIATE MARKETING, LIVE STREAMING, AND ONLINE CUSTOMER REVIEWS ON PURCHASING DECISIONS OF FACETOLOGY SUNSCREEN PRODUCTS ON TIKTOK SHOP - Shinta Nuriya; Alshaf Pebrianggara; Hasan Ubaidillah; Misti Hariasih (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to analyze the influence of affiliate marketing, live streaming, and online customer reviews on purchasing decisions for Facetology sunscreen products on TikTok Shop. Method: This research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who have used Facetology products. The data analysis technique used Partial Least Square (PLS) to examine the relationship between variables. Results: The results show that affiliate marketing, live streaming, and online customer reviews have a positive and significant effect on purchasing decisions. Live streaming has the most dominant influence because it provides direct information, increases interaction, and builds consumer trust. Novelty: In addition, affiliate marketing and online customer reviews also play an important role in providing information and recommendations that influence consumer purchasing decisions. This study indicates that digital marketing strategies are effective in increasing purchasing decisions for skincare products on TikTok Shop.